Comparative Law Before 1900 - Mousourakis, George (Revista Amagis Jurídica, 2024)
Modern comparative law emerged in the late nineteenth century primarily as a response to problems caused by the fragmentation of national laws in Europe. Its principal goal was to restore a measure of legal unity and lay the foundations of a science of law that would have the universal character of a genuine science. This paper examines the role of legal comparatism in early modern European legal thought and practice with the view to tracing some key ideas that contributed to the rise of the contemporary comparative law discourse. First, attention is given to the development of the comparative approach to law in the Renaissance and Enlightenment eras – a period marked by the emergence of scientific rationalism and the rise of the modern nation-state and national legal systems. The paper then discusses the contribution of nineteenth century thinkers who endeavoured to explain legal phenomena on a historical-comparative plane and, in this way, paved the way for the recognition of comparative law as a special branch of legal science.